2019
DOI: 10.1177/0363546519877861
|View full text |Cite
|
Sign up to set email alerts
|

How Can We Define Clinically Important Improvement in Pain Scores After Hip Arthroscopy for Femoroacetabular Impingement Syndrome? Minimum 2-Year Follow-up Study

Abstract: Background: Patient postoperative pain is being increasingly reported in the field of hip preservation surgery. The visual analog scale (VAS) for pain is one of the most commonly utilized measures for perioperative pain assessment. Currently, there is limited understanding of clinically significant improvement in VAS pain. Purpose: (1) To define the substantial clinical benefit (SCB), patient acceptable symptomatic state (PASS), and minimal clinically important difference (MCID) for the VAS pain score in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 41 publications
(65 reference statements)
0
50
1
Order By: Relevance
“…43 MCID for the HOS-ADL, HOS-SS, mHHS, and iHOT-12 was determined by calculating the ½ standard deviation of each PROM mean in the study patients, as described in the literature. [44][45][46] When describing achievement of clinically significant outcome, it is generally accepted that this is defined as achievement of MCID on any hip-specific outcome measure. 47,48 The burden of MCID achievement across all outcome measures may not be realistic, given that each outcome measure may represent a separate outcome domain.…”
Section: Functional Outcome Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…43 MCID for the HOS-ADL, HOS-SS, mHHS, and iHOT-12 was determined by calculating the ½ standard deviation of each PROM mean in the study patients, as described in the literature. [44][45][46] When describing achievement of clinically significant outcome, it is generally accepted that this is defined as achievement of MCID on any hip-specific outcome measure. 47,48 The burden of MCID achievement across all outcome measures may not be realistic, given that each outcome measure may represent a separate outcome domain.…”
Section: Functional Outcome Evaluationmentioning
confidence: 99%
“…49 Our methodology here is in line with adopted and accepted FAI, KINESIOPHOBIA, AND PAIN CATASTROPHIZING e99 methods previously reported and supported in the literature. 45,[49][50][51][52] Statistical Analysis All data were screened to determine whether parametric statistical assumptions were met before analysis. In cases of parametric analysis violation, the nonparametric analogue tests were applied.…”
Section: Functional Outcome Evaluationmentioning
confidence: 99%
“…Many authors use the MCID and PASS as a gauge for clinical relevance when determining the significance of their outcomes. 12,15,[17][18][19] Although most percentages of patients achieving MCID and PASS after hip arthroscopy range from 60% to 95% based on the specific score used, 14,17 to our knowledge, no study has used this tool to compare outcomes between opioid-naïve and non-naïve patients undergoing hip arthroscopy. In our study, we demonstrate that opioid-naïve patients are not only statistically more likely to reach the MCID and PASS with regards to the VAS, but also reach these values at an earlier postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…The MCID represents the smallest difference that patients perceive as beneficial 10 and PASS represents the threshold for clinical improvement. 11 Established values of an increase in 8 points for the MHHS, 12 10 points for the NAHS, 13 and a decrease of 1.48 points for the VAS 14 were used. PASS has an established value of 74 points on the MHHS 15 and 2.16 on the VAS.…”
Section: Patient-reported Outcomesmentioning
confidence: 99%
“…Dr. Nho and his colleagues have worked diligently over the past 4 years to establish the MCID, SCB and PASS thresholds for hip-preservation procedures and for hip-related patient-reported outcome measures (PROMs). [4][5][6][7][8][9] Previously establishing these values for young-adult hips, they have shown that 80% of patients achieve significant functional improvements at 2 years following femoral acetabular impingement syndrome (FAIS) surgery. 5 With their latest work, they now establish the MCIDs, SCBs and PASSs for the visual analog scale (VAS) satisfaction score.…”
Section: See Related Article On Page 734mentioning
confidence: 99%